Significados Asignados Por Un Grupo De Padres y Madres, Estudiantes y Docentes en Torno Al Rol Del Psicólogo en el Colegio Montebello de la Ciudad de Bogotá (2016)
In this research work describes the narratives of a group of mothers and fathers and teachers of the College Montebello around the role of the educational psychologist, speeches created from the experiences and meanings attributed versus the professional. The course of the investigation it was created from a qualitative methodological design, epistemologically, it these narratives are addressed from the social constructionism.